Case Report: Combination of focal vibration therapy and botulinum toxin injections to treat equinus gait in a child with unilateral spastic cerebral palsy - Boulay, Christophe; Coq, Jacques-Olivier; Sangeux, Morgan; Authier, Guillaume; Ulian, Alexis; Pradines, Maud; Baude, Marjolaine; Desnous, Béatrice; Jouve, Jean-Luc; Parratte, Bernard; Peltier, Emilie; Pesenti, Sébastien; et al. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionFocal vibration therapy (FVT) is increasingly used in the treatment of spastic paresis. In adults, it has been shown to reduce spasticity and to increase torque production from the vibrated muscles by restoring reciprocal inhibition of antagonists, thereby improving overall gait. In children with spastic cerebral palsy (CP), FVT has also been suggested to reduce spasticity, increase torque production and improve gait function, but evidence is limited.MethodsWe report the case of a child with unilateral spastic CP (USCP) and equinus gait (GFMCS II level) with (i) ankle dorsiflexor paresis, (ii) ankle plantar flexor overactivity, especially in gastrosoleus complex and peroneus longus, (iii) spastic myopathy, affecting gastrosoleus complex in particular, and (iv) calf pain seemingly related to muscle overactivity. The child was treated with a two-month program of alternating dorsiflexor and plantar flexor focal vibration therapy (FVT) and botulinum neurotoxin A (BoNT-A) injections into plantar flexors, alongside conventional physiotherapy.Results and discussionClinical evaluations during the two-month program showed (i) improved walking speed (ii) decreased ankle dorsiflexor paresis and ankle plantar flexor overactivity, especially spastic co-contraction and spasticity, (iii) improved passive extensibility in plantar flexors, and (iv) reduced pain. This is the first report of the combination of FVT and BoNT-A injections having promising effects on equinus gait in USCP.